Women's empowerment through seed improvement and seed governance: evidence from participatory barley breeding in pre-war Syria - Galiè, Alessandra (International Livestock Research Institute, 2017)
Presented by Alessandra Galie (ILRI, formerly ICARDA), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.